2-(2,5-Dichlorobenzenesulfonamido)-3-methylbutanoic acid - Khan, Islam Ullah (International Union of Crystallography, 2010)
The structure of the title compound, C(11)H(13)Cl(2)NO(4)S, shows one sulfonamide-O atom to lie almost in the plane of the benzene ring [C—C—S—O = −178.7 (2) °] and the other to one side [C—C—S—O = −49.4 (3)°]. Lying to the other side is the amine residue, which occupies a position almost perpendicular to the plane [C—S—N—C = 70.2 (2)°]; the carboxylic acid group is orientated to lie over the benzene ring. In the crystal, the appearance of an 11-membered {⋯OH⋯OCOH⋯OC(2)NH} synthon, which features the hydroxy group forming both donor (to a carbonyl-O) and acceptor (from the amine-H) interactions, leads to the formation of a supramolecular chain along the a axis. Chains are connected in the crystal structure by C—H⋯O contacts.